Diseño de una estrategia para el cumplimiento de las actividades de verificación documental en el grupo de agroquímicos en la Autoridad Nacional de Licencias Ambientales (2023)
Within ANLA's operations, the use of agrochemicals is supervised and regulated through documentary verification that supports the environmental compliance of related products. However, it has been detected that most of these procedures face nonconformities, which affects the technical staff and causes significant delays.